Dosimetric effects of inserted non-radioactive elements in a tumor area in proton therapy - Galanakou, Panagiota; Leventouri, Theodora; Muhammad, Wazir (Frontiers in Physics, 2023)
Various Prompt Gamma (PG) rays-based techniques have been proposed to monitor the proton range during the treatment, but the poor PG statistics produced entangle their clinical application. Recently, we developed a Monte Carlo (MC) simulation model for enhancement of the PG production based on the nuclear cross-section of the proton with the material transversed, via inserting the non-radioactive elements 19F, 17O, and 127I in a hypothetical tumor area. To study the dose distribution changes caused by the addition of specific % weight fractions of the PG enhancers in a water medium using MC simulations. Our MC model was created using the TOPAS MC package and keeping identical geometries, mixture compositions, and incident proton energies (75 MeV, 100 MeV, and 200 MeV) previously tested for the PG statistics enhancement. The total dose deposition in water and in mixture compositions that have been found to maximally increase the PG production was scored and evaluated based on the important dosimetric metrics R90, Bragg Peak (BP) width, and FWHM. Further, the spatial correlation of the PG emissions relative to the BPs was also studied and compared on the basis of the BP fall-off at R90. There is no significant change in total dose deposition except for the 127I. However, dose curve shifts in R90 towards shallower depth followed by a steeper BP and reduced FWHM were observed in all cases. The % changes vary with incident proton energies and mixture compositions. The addition of the stable elements had no effect on the PG spatial emission. The dosimetric study reveals that the addition of the tested stable elements did not change the dose distribution and did not alter the dose deposited by secondary particles. Since their addition increases the electron density of the medium, the shift of the BP to shallower depths is linked with the mixture composition changes. Also, a steeper BP is observed which could be beneficial for OAR avoidance. Since this theoretical study of using 19F, 17O, and 127I as PG enhancers is promising from a dosimetric point of view, experimental studies are necessary to determine its clinical application feasibility.